Mengenal Lebih Dekat Dengan Virus Dengue Dan Cara Penanganannya - Rayhana, Rayhana; Anadani, Adinta Anadani; Kharisma, Dayu Swasti; Amin, Noor Latifah; Farhan, Fanny Septiani; Suryanda, Faradillah; Nuban, Yohanis (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Dengue virus is a virus transmitted by mosquitoes namely Aedes aegypti. We educate people about dengue virus and how to handle it so that people, especially endemic areas, can better understand the pattern of dengue virus spread which can cause dengue hemorrhagic fever (DHF) as one of the most deadly diseases. If it continues it can lead to shock due to bleeding. DKI Jakarta area, especially East Jakarta, is one of the endemic areas for DHF. As many as 265 cases of dengue hemorrhagic fever (DHF) have occurred in East Jakarta since the beginning of 2020. The community needs to know more about how to prevent DHF through knowledge of lifestyles where the dengue virus reproduces and how it is transmitted. The local community was very enthusiastic about listening to the counseling, as seen from the satisfaction questionnaire, more than 50% answered that they were satisfied with this counseling.